A scenario analysis of the 2021-2027 European Cohesion Policy in Bulgaria and its regions - Francesca Crucitti; Nicholas-Joseph Lazarou; Philippe Monfort; Simone Salotti (European Commission, Joint Research Centre (JRC), 2021)
We employ the spatial dynamic general equilibrium model RHOMOLO to estimate the economic impact of the 2021-2027 Cohesion Policy in Bulgarian NUTS-2 regions and analyse the implications for growth and development in Bulgaria. The main investment areas covered by the policy fall into the following five fields of intervention: aid to the private sector, research and development, transport infrastructure, other infrastructure, and human capital. They are characterised by a varying degree of positive demand and supply side effects on regional and aggregate development, which, together with the level of the shocks, determine the impact on GDP. We find that a projected exteuro10.9 billion of Cohesion Policy funding would increase Bulgarian GDP by 3.4% above its baseline value at the end of the implementation period in 2030 and by 2.4% ten years later. Our results suggest that there is no systematic equity-efficiency trade-off in Bulgaria which mainly arises as the consequence of low spillovers in the capital city region versus the strictly higher spillovers observed in the rest of the country's regions. We conclude that a balanced Cohesion Policy portfolio would foster a high impact on national GDP, maintain a high intensity of spillovers and reduce regional disparities in Bulgaria.
Keywords: C68; R13; 330; RHOMOLO; Cohesion Policy; regional growth; regional development; Bulgaria